Firms’ corporate social irresponsibility behaviors during interplay with consumers in evolutionary game models - Xiaoyang Zhao; Jie Mi (Humanities & Social Sciences Communications, 2024)
Abstract We employ an evolutionary game model to investigate the interaction between firms’ engagement in corporate social irresponsibility (CSI) behaviors (without violating laws) and consumers’ perception of corporate social responsibility (CSR) within a consumer market. The core paradox revolves around the trade-off between firms benefiting from pursuing economic performance without adhering to social responsibility and the maximization of social welfare achieved when firms are socially responsible, and consumers possess strong CSR perception. Through an asymmetric two-population evolutionary game model, we identify two distinct scenarios of evolutionary stable strategies based on different industrial environments. Additionally, the evolution of a healthy market is contingent upon an increase in consumers’ bargaining power, although it is also influenced by the initial states of the two-group system, resulting in path dependence as a significant feature of the system’s evolutionary equilibrium. Furthermore, we observe that the added willingness to pay for CSR, while not impacting the evolutionary outcomes, could increase the likelihood of a healthy market when consumers’ bargaining power is high. These findings underscore the diverse dynamics of firms’ CSI behaviors, which depend on transaction costs, industrial structure, and consumers’ willingness to pay, offering valuable insights from a micro perspective.